If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + h = 24 Solving 13 + h = 24 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + h = 24 + -13 Combine like terms: 13 + -13 = 0 0 + h = 24 + -13 h = 24 + -13 Combine like terms: 24 + -13 = 11 h = 11 Simplifying h = 11
| 8+5x+4x=-10 | | -3+4x-x=18 | | -6-5x=-61 | | -10+7x=11 | | a-8=6+5a/3 | | 1/24x3 | | 6x+3=8x-17-4 | | c+40=-35 | | y=4x^2+x+3 | | 4+10x=18+17x | | 38p+7p^2=-15 | | b-4=-20 | | y=x^2/2-3x+3 | | 1/9(8x-27) | | 5x+12=8x+30 | | y=-2x^2+x+4 | | x-2(-6)=10 | | 0=x^2-4x-3 | | 6x+y=5x+2 | | 9(5x-6y)= | | 6x+y=7x-2 | | -1=x^2+2x+3 | | -6-2(y)=10 | | 6x+y=7x-1 | | y=x^2-5x+3 | | R*R=((R-5)*(R-5))+81 | | 7x-1=6x+y | | 3a^2+16a+21=0 | | 7x-1=5x+2 | | y=-x^2-2x+2 | | 7x-2=7x-1 | | x+2(5)=8 |